A State-Owned Enterprise Established to Develop the Maritime Transportation Sector: Maritime Bank Turkish Joint Stock Company - Saya, Mehmet (Journal of Applied And Theoretical Social Sciences, 2022)
Maritime Bank Turkish Joint Stock Company, the foundation of which was laid with the establishment of the Hazine-i Hassa Vapurları İdaresi (Private Treasury of The Ottoman Sultan Ferries Administration) in 1844, it was established in 1951 with the law no. 5842, with the idea of ​​developing the maritime transport sector and that it is necessary in terms of national economy, national defense and social necessity during the Democrat Party era. In addition to carrying out all kinds of banking transactions related to maritime transportation, it started its activities in 1952 by being authorized to provide all kinds of convenience especially to real and legal entity engaged in shipbuilding, repair, purchasing, and maritime operations. Since it is a banking-supported organization for the development of maritime transportation, it has been an important topic in terms of both Turkey's economic history and maritime trade history. Therefore, this study focused on the establishment of Maritime Bank Turkish Joint Stock Company. The aim of the study is to analyze the founding venture of this institution by making a descriptive analysis of the documents accessed as secondary sources as well as the primary sources obtained from the archive of the said institution.